Determining the properties of multi-range semi-tubular self-piercing riveted joints - Kappe, Fabian; Wituschek, Simon; Bobbert, Mathias; Meschut, Gerson (Production Engineering, 2022)
By applying a variety of strategies, including both the development of new drive concepts as well as the use of lightweight constructions, it is intended to meet the climate targets set by the Paris Agreement. Multi-material design is often used when applying lightweight constructions, especially in the mobility sector. Herby, various materials with different properties are combined to well adapt the structure to the application of force in order to reduce weight. For example, this can result in the combined use of (high-strength) steel and aluminium. However, the increasing number of materials used and the number of resulting joints has led to the development of a number of different joining processes. These can only be used to a limited extent for joining multi-material joints and are usually inflexible facing changing boundary conditions. Examples of further difficulties affecting the established processes are metallurgical incompatibilities, which particularly pose difficulties for the use of thermal joining processes. A frequently used mechanical joining process is self-piercing riveting. Due to its high load-bearing capacities, a wide range of application and high process robustness it is often used when joining of dissimilar material is required. However, in case of self-piercing riveting used, the increasing number of multi-material joints and material-thickness combinations leads to the need of a large number of rivet-die-combinations to adapt the joining process to the respective joining task. Since the joining system cannot react to these changes, a tool change or an adjustment of the system is necessary, which leads to a reduction in efficiency and extended process times. To increase flexibility and process efficiency, new, versatile joining technologies are needed that can be adapted to changing boundary conditions. One possibility for this is the use of multi-range capable semi-tubular self-piercing rivets, which are inserted into the joint by using a new joining system with extended punch-sided actuator technology. The increased actuator technology enables the rivet to be set by an inner punch and subsequently to form a rivet head by embossing with an outer punch. All punch movements can be controlled independently of each other, enabling adaptive adjustment of the process parameters. Depending on the rivet geometry used, rivet head formation by the outer punch can be performed both with and without head deformation. The rivet without head deformation consists of a tubular shape with ring grooves in the rivet head area. Using the outer punch, punch-sided material is formed into the ring grooves creating an interlock in the head area of the rivet. The rivet with head deformation is designed differently. It is modified to enable subsequent forming to the respective thickness of the joint by forming the protrusion of the rivet head onto the punch-sided joining part. In the study presented here, the joining process of the versatile self-piercing riveting is presented, analysed and the property profile of the joints is determined on the basis of various material-thickness combinations. Here, both the characteristic parameters of the joints and the joint load-bearing capacities are determined. Finally the property profiles are compared with conventionally manufactured joints in order to identify potential for improvement.
CRIS-Team WoS Importer:2022-02-18